Penerapan Pendekatan Deep Learning Berbasis Gimkit Terhadap Kemampuan Berpikir Kritis - Diah Ayu Rahmawati; Hevy Risqi Maharani (Pendidikan Matematika FKIP Universitas Mataram, 2026)
Students' critical thinking skills in mathematics learning are still relatively low, particularly in algebraic operations. This study aimed to analyze the effectiveness of a gimkit web-based deep learning approach in improving students' critical thinking skills. This research employed a quantitative method using a one-group pretest–posttest design involving 27 seventh-grade students of SMP Islam Sultan Agung 4 Semarang. Data were collected through tests, observations, and response questionnaires. The data analysis techniques included normality testing, individual and classical learning mastery analysis, and N-Gain calculation. The results showed a significant improvement in students' scores after the implementation of the treatment. Learning mastery was achieved both individually and classically, and the improvement in critical thinking skills was categorized as high. Furthermore, both teachers and students gave positive responses to the learning process. Therefore, the Gimkit web-based deep learning approach was effective in improving students' critical thinking skills.